The effects of investment, monetary policy, and ZIS on economic growth in Indonesia - Musalim Ridlo; Laeli Dwi Wardani (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
This study's background is an effort from the government to implement economic stabilization from economic growth instruments. Economic growth is influenced by economic factors such as investment, monetary policy, zakat, infaq, and sadaqah (ZIS). This study analyses investments, monetary policy, and ZIS (Zakat, Infaq, Sadaqah) on economic growth in the Indonesia period of 2013-2018. The Data collection method is done through data retrieval from the Statistical Center (BPS), Financial Services Authority (OJK), Bank Indonesia (BI), the National Amil Zakat Agency (BAZNAS). This study uses the linear regression method. The results of this research show that mutual fund (investment) has a negative effect, the exchange rate (monetary policy) has not significant, and ZIS (Zakat, Infaq, Sedekah) has not signed on economic growth in Indonesia